Preschool teachers’ ideas about practices to promote peer relations: Using Q methodology to determine viewpoints - Gamelas, A. (2022)
An internationally accepted definition of early childhood inclusion includes the right to achieve a sense of belonging and membership, positive social relationships, and friendships. Although Portuguese preschool curriculum guidelines value childchild interactions as an outcome by itself and as means to achieving other development and learning outcomes it does not explicitly mention social participation indicators. Additionally, information is lacking on Portuguese preschool teachers’ beliefs, priorities, and practices specifically related to the support of peer relations. This study was developed in the scope of the project Enhancing peer relationships: Preschool teachers' ideas and practices. One of its goals is to understand Portuguese preschool teacher’s ideas about what is important in supporting peer interactions, relationships, and group membership, for children with and without disabilities. To pursue this goal Q methodology was applied. We developed a Q sample consisting of 74 items that reflect a range of possible interventions targeted at enhancing social inclusion and peer interactions and relationships. The P sample was composed by 43 preschool teachers and their individual Q sorts were subjected to principal components analyses (PCA) followed by varimax rotation. A seven-component solution, explaining 55.5% of the variance, was considered the starting point for the decision-making process on the number of components to be considered as the best solution. Both statistical and conceptual criteria are being used to determine the final number of viewpoints. This presentation describes this decision-making process and the results will be discussed according to their implications for the global project.